Beneficial effects of dual vascular endothelial growth factor receptor/fibroblast growth factor receptor inhibitor brivanib alaninate in cirrhotic portal hypertensive rats. Issue 5 (May 2014) - Lin, Han‐Chieh; Huang, Yi‐Tsau; Yang, Ying‐Ying; Lee, Pei‐Chang; Hwang, Lih‐Hwa; Lee, Wei‐Ping; Kuo, Ying‐Ju; Lee, Kuei‐Chuan; Hsieh, Yun‐Cheng; Liu, Ren‐Shyan
Abstract Background and Aim Vascular endothelial (VEGF) and fibroblast growth factor (FGF)‐induced hepatic stellate (HSCs) and liver endothelial cells (LECs) activation accelerates hepatic fibrogenesis and angiogenesis, and hemodynamic dysarrangements in cirrhosis. VEGF targeting agents had been reported as potential drugs for cirrhosis. However, the evaluation of effects of dual VEGF/FGF targeting agent in cirrhosis is still limited. Methods Using hemodynamic parameters, blood chemistry, primary isolated HSCs and LECs, histology, and digital imaging, we assess the effects of 2‐week brivanib alaninate, a dual VEGFR/FGFR inhibitor, treatment in the pathophysiology of bile duct‐ligated‐cirrhotic rats. Results Fibrogenic and angiogenic markers in the serum and liver of bile duct‐ligated‐cirrhotic rats, including hydroxyproline, transforming growth factor‐β1, angiopoietin‐1, VEGF, FGF‐2, endocan and phosphorylated‐VEGFR2/VEGFR2, and phosphorylated‐FGFR/FGFR together with hepatic CD31/angiopoietin‐1 expressions (immunohistochemistry staining), angiogenesis (micro‐computed tomography scan), microcirculatory dysfunction (in vivo miscroscopy and in situ liver perfusion study), portal hypertension, and hyperdynamic circulations (colored microsphere methods) were markedly suppressed and ameliorated by brivanib alaninate treatment. In in vitro study, acute brivanib alaninate incubation inhibited the transforming growth factor‐β1‐induced HSCs contraction/migration and VEGF‐induced LECs angiogenesis. Concomitantly, the overexpression of various fibrogenic and angiogenic markers in HSCs and LECs, and in their culture media, was increased in parallel and these changes were suppressed by acute brivanib alaninate incubation. Conclusions This study demonstrated that brivanib alaninate targeting multiple mechanisms and working in the different pathogenic steps of the complications of cirrhotic rats with portal hypertension.